High resolution copy number analysis of IRF4 translocation-positive diffuse large B-cell and follicular lymphomas - Salaverria, Itziar; Martin-Guerrero, Idoia; Burkhardt, Birgit; Kreuz, Markus; Zenz, Thorsten; Oschlies, Ilske; Arnold, Norbert; Baudis, Michael; Bens, Susanne; García-Orad, Africa; Lisfeld, Jasmin; Schwaenen, Carsten; et al. (Genes, chromosomes & cancer, 2013)
Translocations affecting chromosome subband 6p25.3 containing the IRF4 gene have been recently described as characteristic alterations in a molecularly distinct subset of germinal center B-cell-derived lymphomas. Secondary changes have yet only been described in few of these lymphomas. Here, we performed array-comparative genomic hybridization and molecular inversion probe microarray analyses on DNA from 12 formalin-fixed paraffin-embedded and two fresh-frozen IRF4 translocation-positive lymphomas, which together with the previously published data on nine cases allowed the extension of copy number analyses to a total of 23 of these lymphomas. All except one case carried chromosomal imbalances, most frequently gains in Xq28, 11q22.3-qter, and 7q32.1-qter and losses in 6q13-16.1, 15q14-22.31, and 17p. No recurrent copy-neutral losses of heterozygosity were observed. TP53 point mutations were detected in three of six cases with loss of 17p. Overall this study unravels a recurrent pattern of secondary genetic alterations in IRF4 translocation-positive lymphomas. © 2012 Wiley Periodicals, Inc.
First published: 17 October 2012
Gesehen am 26.01.2022